Thermo-catalytic co-pyrolysis of palm kernel shell and plastic waste mixtures using bifunctional HZSM-5/limestone catalyst: Kinetic and thermodynamic insights - Chee, April Ling Kwang; Chin, Bridgid Lai Fui; Goh, Sharon Meng Xuang; Chai, Yee Ho; Loy, Adrian Chun Minh; Cheah, Kin Wai; Yiin, Chung Loong; Lock, Serene Sow Mun (2023)
Kinetic and thermodynamic parameters of catalytic co-pyrolysis of palm kernel shell (PKS) and high-density polyethylene (HDPE) with three different catalysts (zeolite HZSM-5, limestone (LS) and bifunctional HZSM-5/LS) using thermogravimetric analyser via nitrogen environment were studied. The experiments were carried out at different heating rates ranging from 10 to 100 K/min within temperature range of 50–900 °C. Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS) and modified Distributed Activation Energy Model (DAEM) methods were employed in this current study. The average Ea for PKS, HDPE, PKS/HDPE (2:8) – HZSM-5, PKS/HDPE (2:8) – LS, PKS/HDPE (2:8) – HZSM-5/LS, PKS/HDPE (5:5) – HZSM-5/LS, PKS/HDPE (8:2) – HZSM-5/LS are 137.26–145.49, 247.73–250.45, 168.97–172.50, 149.74–152.79, 115.30–120.39, 124.36–129.41, 151.03–154.47 and 152.67–157.31 kJ mol−1, respectively. Among the different catalysts used, LS demonstrated the lowest average Ea (151.30–120.39 kJ mol−1) and ΔH (109.65–114.74 kJ mol−1). Positive values for ΔH and ΔG were found for the catalytic co-pyrolysis of PKS/HDPE mixtures which indicates the process is in endothermic reaction and possess non-spontaneous nature. The kinetic and thermodynamic analyses revealed the potential of PKS and HDPE as a potential feedstock for clean bioenergy production.